Correction to Gofen (2013): "Powers which commute or associate as solutions of ODEs?", Teaching Mathematics and Computer Science 11 (2013), 241-254. - Gofen, Alexander (Teaching Mathematics and Computer Science, 2022)
In the article "Powers which commute or associate as solutions of ODEs?" by Alexander Gofen (Teaching Mathematics and Computer Science, 2013, 11(2), 241–254. https://doi.org/10.5485/TMCS.2013.0347), there was an error in Conjecture 1 (p. 250), and consequently, in the References (p. 254).